Laporan Pembentangan Dalam Persidangan “The 7th International Conference On Islam In Malay World (ICON-IMAD VII) : Strengthening the Moderate Malay Islam in Southeast Asia” - Lilly Suzana Shamsu (AR-RĀ’IQ, 2018)
Laporan Pembentangan Dalam Persidangan